IDENTIFIKASI WASTE PADA WHOLE STREAM PERUSAHAAN ROKOK DI PT.X16 - Rakhmawati Rakhmawati (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
Identify to be done by using method of lean manufacturing. This research aimed at identify waste and formulate effort reduction of waste production process smoke in PT.X. The data were collected from manufacturer records, study to determine processing time, as well as interview and quisioners which were distributed to workers in each department. Big picture mapping and value stream mapping tools (VALSAT) were then utilised to process the data.Result of from research got that during once production process can reduce from 152.59 minute become 149.59 time and minute every order 26 day become 19 day. From result of waste workshop known that type extravagance of cause the happening of production process time depth ( 3 highest ) is defect, waiting time and excessive transportation, so that appliance (tool) matching with the extravagance type is mapping filter quality with successive wight 96,6 : 55,86 : and 23,32.According to the result found also cause of extravagance for example, to the number of time used for the activity of inspection between aktifitas so that cause production process time become Ilama, existence of distance which among tobacco warehouse with process of perajangan resulting the happening of movement of bolak return worker so that add production process time become llama. One of the ways to improve it is by applying pull system (Kanban).